REFORMING MEMORY: ESSAYS ON SOUTH AFRICAN CHURCH AND THEOLOGICAL HISTORY - H van der Westhuizen (Acta Theologica)
Henco van der Westhuizen reviews a book from VOSLOO, R. (Stellenbosch: African Sun Media, 2017). 287 pp. ISBN: 978-1-9283-14-36-3.